Effect of forging load and heat treatment process on the corrosion behavior of A588-1%NI for weathering steel application in a marine environment - Miftakhur Rohmah; Permana Andi Paristiawan; Toni B. Romijarso (Universitas Mercu Buana, 2022)
The study focused on the effect of forging load and heat treatment on the corrosion behavior of A588-1%Ni weathered steel. The samples used were hot forged steel (A588%-1%Ni) with a load of 50 tons and 75 tons at a temperature of 800-850 °C. The test sample was reheated at an intercritical temperature between A3–A1, around 780 °C, held for 1 hour, and then cooled to room temperature. The cooling media used are water, oil, and open air. Forging loads and heat treatment variation affect the microstructure and corrosion rate of A588-1%Ni. Based on the metallographic test and after the hot forging process, A588-1%Ni laterite steel has a microstructure as ferrite-perlite. Then, after heat treatment as ferrite and cementite-containing phase, pearlite, bainite, or martensite may very well. Cooling water delivers a uniformly distributed lath martensite with an acicular ferrite phase. In addition, the oil media creates bainite with an acicular ferrite phase coarser size. The open-air media produces a pearlite + ferrite phase. Corrosion behavior of laterite steel subjected to hot forging process and followed by heat treatment was evaluated in 3% NaCl solution. Oil cooling with bainite-ferrite microstructure has the lowest corrosion rate, which is 11.96x10-3 mmpy.